Identification and Experimental Study of Sand Gravel Formations Driven by an Earth Pressure Balance Shield Machine Based on GTNet - Peng Zhou; Qian Wang; Ziwen Wang; Jiacan Xu; Zi Wang (Applied Sciences)
The earth pressure balance shield machine (EPB) is an important piece of engineering equipment used in tunnel excavation and plays an important role in large underground tunnel projects. This article takes the sand and gravel formation as the research object, while discrete element simulation is utilized to study the correlation between cutterhead torque and thrust and other parameters. The EPB tunneling experiment was carried out by setting up formations with different sand and gravel contents. The reliability of the simulation model was verified by the experimental data, which provided the data samples for the training of the excavation formation identification network. Finally, a GTNet (gated Transformer network) based on the formation identification method was proposed. The reliability of the network model was verified by contrasting the model used with other network models and by analyzing the results of experiment and visualization. The effects of different parameters were weighted using the ablation study for tunneling parameters. The proposed method has a high accuracy of 0.99, and the cutterhead torque and thrust have a great recognition feature, the weight of which is over 0.95. This paper can provide significant guidance for the torque and thrust analysis of cutterheads in tunnel construction.